Two notions of rigidity - Rumfitt, I (Routledge, 2024)
I argue for recognizing a semantic category of designators. Some designators are rigid while others are not. In explaining the notion of rigidity, we should not follow Saul Kripke and invoke possible worlds. Rather, we should follow Richard Cartwright and say that the designator ‘a’ is rigid if and only if neither the sentence ‘a might have existed and not have been identical with a’ nor the sentence ‘Something other than a might have been identical with a’ has an interpretation on which it is true. I contrast this with a notion whereby ‘a’ is quasi-rigid if and only if there is an object x such that it is constitutive of the meaning of ‘a’ that ‘a’ designates x. Gareth Evans's descriptive name ‘Julius’ is, I argue, rigid but not quasi-rigid. Finally, I put the notion of quasi-rigidity to use in elucidating Evans's distinction between deep and superficial necessity.